Background noise : perspectives on sound art - LaBelle, Brandon (New York : Continuum International, 2006)
Fade in -- ##Pt. I. 4'33": sound and points of origin. Sociality of sound: John Cage and musical concepts ; Exposing the sound object: Musique Concrète's sonic research ; Automatic music: Group Ongaku's performative labors -- ##Pt. 2. Box with the sound of its own making: from gags to sculptural form. Rhythms of chaos: happenings, environments, and fluxus ; Minimalist treatments: La Monte Young and Robert Morris ; Conceptualizations: Michael Asher and the subject of space -- ##Pt. 3. I am sitting in a room: vocal intensities. Performing desire/performing fear: Vito Acconci and the power plays of voice ; Finding oneself: Alvin Lucier and the phenomenal voice ; Word of mouth: Christof Migone's Little Manias -- ##Pt. 4. Public supply: buildings, constructions, and locational listening. Tuning space: Max Neuhaus and site-specific sound ; Other architectures: Michael Brewster, Maryanne Amacher, and Bernhard Leitner ; Composing intensities: Iannis Xenakis's multimedia architectures -- ##Pt. 5. Soundmarks: environments and aural geography. Seeking ursound: Hildegard Westerkamp, Steve Peters, and the soundscape ; Language games: Yasunao Tone and the mechanics of information ; Complicating place: Bill Fontana and networking the soundscape -- ##Pt. 6. Global strings: interpersonal and network space. Interactions: Achim Wollscheid's production of the local ; Global events: Atau Tanaka and network as instrument ; Live streams: Apo33 and multiplying place -- ##Fade out --
boek